Role of institutional changes in the sphere of higher education in the social-economic development of a region (by the example of Rostov oblast) - A. I. Maskaev; P. O. Savko (Russian Journal of Economics and Law)
Objective: to formulate the principles of reforming the industry and to identify the relationship between the universities reorganization and the indicators of socio-economic development of a region.Methods: questionnaires, in-depth interviews, econometric modeling, supplementation of Balatsky model.Results: the theoretical framework of the current reforms in the sphere of national higher education is, on the one hand, the concept of new public management (NPM), which assumes the implementation of market mechanisms in the management of universities, and on the other hand, the trends and development conditions of knowledge economy - the modern stage of post-industrial society. The article presents the results of the analysis of approaches to the NPM concept, identifies its essential characteristics, as well as features of implementation in the system of higher education, identifies the main causes and vectors of transformations in higher education. In the context of the analyzed scientific works in the modern Western and Russian discourse, much attention is given to the “third mission” of university. Theoretical developments in interrelation between higher education reforms and social and economic development of the region are considered. The results are presented of analysis of organizational change and evaluation of the contribution of the reformed universities in the regional economy by the example of Rostov region, obtained from questionnaires and in-depth interviews and using a modified Balatsky model. Conclusions about the problems of the reforms from the viewpoint of teaching and managing personnel of the reformed universities are formulated. Scientific novelty: the conceptual conclusions of the authors allow supplementing the original institutional theory in the field of the relationship between institutional changes and economic development, including the proposed application of Balatsky model for quantitative metrics of the resulting effects of changes in higher education in the socio-economic development of a region. Practical significance: the research results have potential application in the development of reforms in the framework of the action plan (roadmap) of the government of the Russian Federation “Changes in social sphere aimed at improving the efficiency of education and science”.